Comportamiento de componentes agronómicos y de rendimiento bajo dosis creciente de gallinaza en Solanum melongena L. “berenjena”, en Zungarococha-Loreto. 2021 - Pasmiño Vasquez, Mayra Chachy (2022)
The trial “Behavior of agronomic and yield components under increasing doses of chicken manure in Solanum melongena L. “aubergine”, in Zungarococha-Loreto. 2021 was formalized at the facilities of the Horticultural Plant Teaching and Research Workshop (TEIPH), of the Faculty of Agronomy-UNAP, located in the District of San Juan Bautista, Province of Maynas-Loreto, where the height of the plant, the Diameter of the plant, Length of the fruit, Diameter of the fruit, Weight of the fruit, Number of fruits/plant, Weight of fruits/plant and Weight of fruits/ha). The objective was to determine the behavior of the agronomic and yield components under increasing doses of chicken manure in Solanum melongena L. “aubergine”. The Statistical Design used was the Completely Randomized Block Design, with four treatments and four repetitions. Each experimental unit was made up of 2 rows, 4 plants/row and the sampling unit was made up of four plants/experimental unit. At the end of the experiment, the following conclusions were reached: The increasing doses of chicken manure in the cultivation of Solanum melongena L. “eggplant” influenced the agronomic components and yield; Treatment T4 (60 t of chicken manure/ha), obtained the highest average values of the agronomic components and crop yield, Treatment T4 (60 t of chicken manure/ha), presented the best average value of fruit weight yield/ ha with 14,159,292 Kg/ha; Treatment T4 (60 t of chicken manure/ha), presented the best Benefit-Cost relationship of the crop with a profit of S/. 56,331.46